2016
DOI: 10.1088/1361-648x/29/7/07lt01
|View full text |Cite
|
Sign up to set email alerts
|

FIB synthesis of Bi2Se31D nanowires demonstrating the co-existence of Shubnikov–de Haas oscillations and linear magnetoresistance

Abstract: Since the discovery of topological insulators (TIs), there are considerable interests in demonstrating metallic surface states (SS), their shielded robust nature to the backscattering and study their properties at nanoscale dimensions by fabricating nanodevices. Here we address an important scientific issue related to TI whether one can clearly demonstrate the robustness of topological surface states (TSS) to the presence of disorder that does not break any fundamental symmetry. The simple straightforward meth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 28 publications
5
31
0
Order By: Relevance
“…Note that the rise or decay time constant values are estimated here either using the exponential rise or decay fit equations. However we find that rise time or decay time constants in ms are in good agreement (Table 1 ) with the published literature and show competitiveness for photodetector applications and the fast response indicate the efficient carrier transport facilitated may be due to the robust nature of the TSS and high mobility 25 , 26 which is far better as compared with the transition metal dichalcogenides 27 , 28 . The broad spectral photodetection based on nanobelts, nanoribbons, nanosheets and emerging 2D materials have been recently published in a review article 29 .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Note that the rise or decay time constant values are estimated here either using the exponential rise or decay fit equations. However we find that rise time or decay time constants in ms are in good agreement (Table 1 ) with the published literature and show competitiveness for photodetector applications and the fast response indicate the efficient carrier transport facilitated may be due to the robust nature of the TSS and high mobility 25 , 26 which is far better as compared with the transition metal dichalcogenides 27 , 28 . The broad spectral photodetection based on nanobelts, nanoribbons, nanosheets and emerging 2D materials have been recently published in a review article 29 .…”
Section: Discussionsupporting
confidence: 86%
“…Huang et al . observed that transport through TSS can tolerate the surface oxidation and molecules absorbed on the samples surface 40 and our previous work also showed the robustness of TSS towards the Ga ion milling and inherent material deformations 26 , 41 .…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Currently, Bi 2 Te 3 insulator material is generally produced by mechanical exfoliation and molecular beam epitaxy . Meanwhile, Bi 2 Te 3 thin films could be prepared by pulsed‐laser deposition, and Bi 2 Te 3 nanowires could be fabricated by the focused Ion beam method . However, those growth methods are not simple enough but difficult and great cost, thus it is difficult to industrialize in the microwave absorbing filed.…”
Section: Introductionmentioning
confidence: 99%
“…Recent measurements of photoconductive effects on Bi 2 Te 3 nanosheets and nanowires 12 and on Bi 2 Se 3 nanoflakes 14 and nanowires 15 were attributed to the conduction via topological surface states, mainly due to the large surface-to-volume ratio in these nanodevices. Also, Shubnikov-de Haas oscillations and Aharonov-Bohm interference effects measured on Bi 2 Se 3 nanowires fabricated by focused ion beam milling 33,34 were considered as a manifestation of robust topological surface states in nanostructures of this TI material. Moreover, the robustness of surface states against disorder was demonstrated by the measurement of magnetoconductance oscillations at low temperatures (1.8 K) on Bi 2 Te 3 nanotubes.…”
mentioning
confidence: 99%